A Phase I/II Study of Stereotactic Hypofractionated Once-weekly Radiation Therapy (SHORT) for Prostate Cancer. Issue 2 (February 2020) - Mallick, I.; Arunsingh, M.; Chakraborty, S.; Arun, B.; Prasath, S.; Roy, P.; Dabkara, D.; Achari, R.; Chatterjee, S.; Gupta, S.
Abstract: Aims: Stereotactic radiation therapy has been investigated predominantly in patients with low–intermediate-risk disease. We conducted a clinical trial of stereotactic hypofractionated radiation therapy delivered in once-weekly fractions on patients with all-risk non-metastatic disease to test feasibility, acute toxicities and patient-reported outcomes. Materials and methods: In this phase I/II study, 30 patients with prostatic adenocarcinoma, any Gleason score, T1-4N0 and prostate-specific antigen ≤60 ng/ml were treated with volumetric intensity modulated arc radiation therapy to a dose of 35 Gy in five fractions delivered once weekly. Patients with high-risk disease also received elective nodal irradiation to a dose of 25 Gy in five fractions simultaneously. Androgen deprivation was offered to intermediate- and high-risk patients. The primary outcome was acute toxicity. Secondary outcome measures included biochemical control and late toxicity. Patient-reported outcomes were measured using the International Prostate Symptom Score and European Organization for Research and Treatment of Cancer (EORTC) Quality-of-Life Questionnaire (QLQ). Results: All 30 patients completed treatment per-protocol. Most patients had T3 (60%) and Gleason 7 (50%) tumours. The median prostate-specific antigen was 17 ng/ml. High-risk disease was present in 20 patients (66.7%). There was a low incidence of acute toxicities (grade 2 + urinary 3.3%, grade 2 rectal 0%). Within the EORTC QLQ framework, only the urinary symptom score showed a clinically meaningful worsening from a mean of 20/100 at baseline to 34/100 at the end of treatment ( P  < 0.001), but reduced to 24/100 at 6 months ( P  = 0.08). With a median follow-up of 41.5 months, two patients each reported grade 2 late urinary and rectal toxicity. The 3- and 4-year biochemical control rates were 96.7 and 87.9%, respectively. Conclusion: In a cohort of mainly high-risk cancers, stereotactic once-weekly radiation therapy was easy to implement and well tolerated, with a low incidence of acute and late toxicity and excellent biochemical control. Highlights: Prospective phase I/II clinical trial of stereotactic body radiotherapy in node-negative prostate cancer. Patients were predominantly high risk or very high risk by NCCN criteria. Dose prescribed was 35 Gy in five fractions once a week with elective nodal radiation of 25 Gy in five fractions. Acute and late toxicities were low. The 3- and 4-year biochemical control rates were 96.7% and 87.9%.